A Comparison of Genre, Lexile, and Word Count of Read-Aloud Texts in Core Reading Series - Catherine Rand (Journal of Elementary and Secondary School, 2026)
This quantitative content analysis compares the Lexile level, estimated volume, and genre of Year Five and Six read-aloud texts used in four popular US core reading series to analyze the similarities between programs focusing on word count, Lexile level, and genre. The four series include Houghton Mifflin Harcourt’s Into Reading, Lucy Calkins’ Units of Study for Teaching Reading, Fountas & Pinnell’s Classroom Collection, and McGraw-Hill’s Wonders. Descriptive statistics showed considerable differences between programs, including low mean Lexile levels, considerable differences in volume of text, and too little informational text across all programs. These findings align with other scholars’ critiques over the last 20 years. This data is important in understanding the effects of curriculum on comprehension and reading growth, as well as the equity of reading opportunities given to students.